The Pragmatic Analysis Of Maxim Flouting In Sri Mulyani`S Interview On Deutsche Welle News Show - Angela Derta Praptan Nyani; Agustinus Harry Setyawan (Jurnal Dunia Pendidikan, 2023)
This research is a pragmatic analysis of maxim flout in Deutsche Welle Show in which Sri Mulyani became a guest star in the program. This present study aims to analyze the types of maxims that are flouted in Deutsche Welle Show and to describe functions of maxim flouting conducted by the host and the guest speaker in the show by employed a conceptual framework of Griece`s cooperative principle of flouting maxims to analyze the data (Geis et al., 1976). The method of this research was qualitative by applying the utterances in the video conversation from the talk show. Meanwhile, the study`s instrument was the transcript text of the utterances that occurred between the host and Sri Mulyani as a guest star consisting of flouting maxims by. The finding shows 8 flouting maxims in the interview. There were 3 flouting maxim of quantity, 2 flouting maxim of quality, 1 flouting maxim of relevance and 2 flouting maxim of the manner. The data analysis was carried out by identifying the data into the types and functions of maxim flouting. The study found that all types of maxim are flouted in the talk show.